Influence of the Weight Ratio of an Epoxidimethacrylate Oligomer and 1,6-Hexanediol Diacrylate Monomer on Photocrosslinking and Properties of UV-Cured Coatings - Nguyen, Thien Vuong; Le, Xuan Hien (Old Journal, 2020)
Influence of the weight ratio of an epoxidimethacrylate oligomer (EDMA) and 1,6 hexanediol diacrylate monomer (HDDA) on photocrosslinking and properties of UV-cured coatings have been studied. The obtained results showed that the decrease of the EDMA/HDDA ratio from 80/20 to 20/80 led to an increase in the rate of consumption of acrylate groups upon UV-exposure. The systems with EDMA/HDDA ratios ranged from 60/40 to 40/60 can be easily applied to form fine coatings on glass and steel CT3. These coatings have an obvious difference in relative hardness after 0.3 s of UV-exposure but no significant difference in properties after 1.2 s of irradiation with gel fraction, swelling degree, relative hardness, impact resistance, flexibility, adhesion and gloss at 60° of 92%; 476 ÷ 457 g; 0.92 ÷ 0.90; 20 ÷ 30 KG.cm; 20 mm; point of 5 and 100%.